Nutrient omission on growth and leaf contents of blackberry - Farias Barreto, Caroline; Navroski, Renan; Benati, Jorge Atilio; Irribarem Costa, Savana; Nava, Gilberto; Correa Antunes, Luis Eduardo (Comunicata Scientiae, 2022)
Cultivation of blackberry has gradually expanded in Brazil, due to their rusticity and low production cost; thus, it stands out as an excellent option for product diversification. There is a need to improve technical information on the management of this crop, especially mineral nutrition. Knowledge of the visual symptoms of nutritional deficiency and foliar contents of the nutrients allows helps farmers to choose the most adequate fertilization for plants. This study aimed at evaluating nutritional aspects and effects of nutrient omission on the growth of BRS Xingu blackberry. Treatments consisted of complete solutions and individual omission of the following nutrients: nitrogen (N), phosphorus (P), potassium (K), calcium (C), magnesium (Mg), boron (B), manganese (Mn), zinc (Zn) and iron (Fe). The following variables were evaluated: leaf dry matter, root dry matter, total dry mass, macro- and micronutrients contents in leaves and visual symptoms of nutrient deficiency. Macronutrient and B deficiencies limit growth of blackberry. B omission led to the highest decrease in plant growth, besides leaf wrinkling, a fact that shows that BRS Xingu is susceptible to its deficiency. Correlation was found between N and Ca, N and P and B and Ca leaf contents. Low leaf contents of N, K, Ca and B were observed when these nutrients were omitted from the solution.